Effect of Auxins on Root formation in the Vegetative Propagation of Populus alba, Populus tremula, Picea abies and Juniperus Communis - Al-Kinany, Adil (Indian Forester, 1981)
During the course of training in GDR, vegetative propagation of Populus alba, Populus tremula, Picea abies and Juniperus communis by cuttings using different concentrations of IBA and NAA singly as well as in mixture was studied from February, 1979 to June, 1979 under glass house conditions at the Department of Biology, Dresden Technical University, Dresden. The choice of the species for this work was predominantly guided by their close similarity in silvicultural behaviour with the economically important species of Iraq. The IBA and NAA treatments of the four experiments were laid in randomized complete block design, each treatment being replicated three times with 18-20 cuttings per replication. The results of the study showed that IBA upto 4000 ppm alone and upto 2000 ppm in mixture with NAA, highly significantly increased the survival percentage of the rooted cuttings of Populus alba, while IBA upto 200 ppm had a significant effect in terms of increasing the number of branches and leaves, and the fresh and dry weight of whole stems as well as roots. The experimental results of Populus tremula cuttings indicated that there are bright prospects of boosting their rooting and survival percentage by using higher concentrations than 2000 ppm of IBA alone or in mixture with NAA. With Picea abies, through IBA at 4000 ppm gave better survival percentage and number of roots per plant than 200 ppm or control, yet the differences among these treatments were non-significant. However, there are indications of obtaining promising results if higher concentrations than 4000 ppm are tried. The work with Juniperus communis cuttings showed encouraging results in survival percentage with IBA at 4000 ppm and pointed to the need for trying higher concentrations than this in order to enhance the survival percentage of rooted cuttings still further.